Do Children Benefit from Internet Access? Experimental Evidence from Peru - Ofer Malamud; Santiago Cueta; Julian Cristia; Diether W. Beuermann (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper provides experimental evidence for the impact of home internet access on a broad range of child outcomes in Peru. We compare children who were randomly chosen to receive laptops with high-speed internet access to (i) those who did not receive laptops and (ii) those who only received laptops without internet. We find that providing free internet access led to improved computer and internet proficiency relative to those without laptops and improved internet proficiency compared to those with laptops only. However, there were no significant effects of internet access on math and reading achievement, cognitive skills, self-esteem, teacher perceptions, or school grades when compared to either group. We explore reasons for the absence of impacts on these key outcomes with survey questions, time-diaries, and computer logs.
Keywords: I21; 330; internet; children; education; skills; experimental; Peru